2010
DOI: 10.1038/ijo.2010.50
|View full text |Cite
|
Sign up to set email alerts
|

The impact of perinatal probiotic intervention on the development of overweight and obesity: follow-up study from birth to 10 years

Abstract: Background: The achievements in combating the increasing trend of overweight and obesity have thus far been inadequate. The recently discovered instrumental role of the gut microbiota in host metabolism may offer a novel target in the prevention and management of obesity. Objective: To evaluate the impact of perinatal probiotic intervention on childhood growth patterns and the development of overweight during a 10-year follow-up. Patients and methods: Altogether 159 women were randomized and double-blinded to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
182
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(197 citation statements)
references
References 40 publications
7
182
0
8
Order By: Relevance
“…A recent meta-analysis showed a significant reduction in the prevalence and incidence of atopic eczema in children aged 2-7 y whose mothers received probiotics during pregnancy (74). In line with these observations, a recent finding has shown that perinatal probiotic intervention was able to moderate the excessive weight gain during childhood, the impact being higher at 4 y of life (75). Furthermore, placenta and fetal immune physiology may be modulated by specific probiotic maternal dietary intervention (76) and also, probiotics consumption can modulate the composition of immune molecules such as transforming growth factor (TGF)-β2 present in breast milk (77,78).…”
Section: Diet and Microbes: Tools To Modify Early Microbial Expositionsupporting
confidence: 67%
“…A recent meta-analysis showed a significant reduction in the prevalence and incidence of atopic eczema in children aged 2-7 y whose mothers received probiotics during pregnancy (74). In line with these observations, a recent finding has shown that perinatal probiotic intervention was able to moderate the excessive weight gain during childhood, the impact being higher at 4 y of life (75). Furthermore, placenta and fetal immune physiology may be modulated by specific probiotic maternal dietary intervention (76) and also, probiotics consumption can modulate the composition of immune molecules such as transforming growth factor (TGF)-β2 present in breast milk (77,78).…”
Section: Diet and Microbes: Tools To Modify Early Microbial Expositionsupporting
confidence: 67%
“…As a probiotic strain, L. rhamnosus applied as a perinatal intervention diminished the initial phase of excessive weight gain in infants (204) , while L. gasseri in fermented milk significantly decreased visceral and subcutaneous fat areas as well as BW of overweight human participants (201) . Potential effects …”
Section: Obesitymentioning
confidence: 99%
“…The reduction in these measurements was also observed in overweight adults after 12 weeks of intervention with L. gasseri SBT2055 (Kadooka et al 2010). In addition, the perinatal use of L. rhamnosus GG was demonstrated to inhibit excessive weight gain in children during the first years of life (Luoto et al 2010).…”
Section: Probioticsmentioning
confidence: 99%